KOMPETENSI KEPRIBADIAN GURU PAK DALAM MEMBENTUK KARAKTER KRISTIANI PESERTA DIDIK - Nappu, Yumita; Manggi, Nelci Oktavianti; Mulyani, Sri (Moriah Theological Seminary, 2024)
Abstract Christian Religious Education (CRE) teachers are not only responsible for teaching religious knowledge. More importantly, PAK teachers serve as living role models. Therefore, possessing superior personality competencies that can serve as a role model, demonstrating love, honesty, discipline, and responsibility, is a primary requirement for a Christian Religious Education (CRE) teacher. This study aims to analyze the role of teachers' personality competencies in shaping students' Christian character. The method used in this research is qualitative. Data collection was carried out through literature studies, drawing from various relevant literature sources. The research results indicate that the personality competence of Christian Religious Education (CRE) teachers is very important in shaping the Christian character of students. Teachers with strong personality competencies can create a conducive learning environment and serve as a real role model for students, enabling them to internalize Christian values. In the process of actualizing personality competencies, there are supporting factors such as a conducive school environment, parental support, professional training, and commitment to Christian values, as well as hindering factors such as lack of training, high workload, low motivation, and the influence of the social environment. Therefore, spiritual guidance and cooperation between schools, churches, and the community are needed so that Christian Religious Education teachers can optimally actualize their personality competencies in shaping students' Christian character. Abstrak Guru Pendidikan Agama Kristen (PAK) tidak hanya berperan sebagai pengajar pengetahuan agama. Namun lebih dari itu, Guru PAK berperan sebagai suri teladan yang hidup. Untuk itu, memiliki kompetensi kepribadian yang unggul, yang mampu menjadi teladan, memiliki kasih, jujur, disiplin, dan tanggung jawab menjadi syarat utama sebagai seorang Guru PAK. Penelitian ini bertujuan untuk menganalisis peran kompetensi kepribadian guru PAK dalam membentuk karakter kristiani peserta didik. Metode yang digunakan dalam penelitian ini adalah metode kualitatif. Pengumpulan data dilakukan dengan studi pustaka, dengan menggali dari berbagai sumber literatur yang relevan. Hasil penelitian menunjukkan bahwa kompetensi kepribadian guru Pendidikan Agama Kristen (PAK) sangat penting dalam membentuk karakter Kristiani peserta didik. Guru yang memiliki kompetensi kepribadian yang kuat mampu menciptakan lingkungan belajar yang kondusif serta menjadi teladan yang nyata bagi peserta didik sehingga peserta didik dapat menginternalisasi nilai-nilai Kristiani. Dalam proses aktualisasi kompetensi kepribadian, terdapat faktor pendukung seperti lingkungan sekolah yang kondusif, dukungan orang tua, pelatihan profesional, dan komitmen terhadap nilai Kristiani, serta faktor penghambat seperti kurangnya pelatihan, tingginya beban kerja, rendahnya motivasi, dan pengaruh lingkungan sosial. Karena itu, diperlukan pembinaan spiritual dan kerja sama antara sekolah, gereja, dan masyarakat agar guru PAK dapat mengaktualisasikan kompetensi kepribadiannya secara optimal dalam membentuk karakter Kristiani peserta didik.